Alteration of N-glycan expression profile and glycan pattern of glycoproteins in human hepatoma cells after HCV infection - Xiang, Tian; Yang, Ganglong; Liu, Xiaoyu; Zhou, Yidan; Fu, Zhongxiao; Lu, Fangfang; Gu, Jianguo; Taniguchi, Naoyuki; Tan, Zengqi; Chen, Xi; Xie, Yan; Guan, Feng; et al. (Biochimica et biophysica acta. General subjects, 2017)
Hepatitis C virus (HCV) infection causes chronic liver diseases, liver fibrosis and even hepatocellular carcinoma (HCC). However little is known about any information of N-glycan pattern in human liver cell after HCV infection. The altered profiles of N-glycans in HCV-infected Huh7.5.1 cell were analyzed by using mass spectrometry. Then, lectin microarray, lectin pull-down assay, reverse transcription-quantitative real time PCR (RT-qPCR) and western-blotting were used to identify the altered N-glycosylated proteins and glycosyltransferases. Compared to uninfected cells, significantly elevated levels of fucosylated, sialylated and complex N-glycans were found in HCV infected cells. Furthermore, Lens culinaris agglutinin (LCA)-binding glycoconjugates were increased most. Then, the LCA-agarose was used to precipitate the specific glycosylated proteins and identify that fucosylated modified annexin A2 (ANXA2) and heat shock protein 90 beta family member 1 (HSP90B1) was greatly increased in HCV-infected cells. However, the total ANXA2 and HSP90B1 protein levels remained unchanged. Additionally, we screened the mRNA expressions of 47 types of different glycosyltransferases and found that α1,6-fucosyltransferase 8 (FUT8) was the most up-regulated and contributed to strengthen the LCA binding capability to fucosylated modified ANXA2 and HSP90B1 after HCV infection. HCV infection caused the altered N-glycans profiles, increased expressions of FUT8, fucosylated ANXA2 and HSP90B1 as well as enhanced LCA binding to Huh7.5.1. Our results may lay the foundation for clarifying the role of N-glycans and facilitate the development of novel diagnostic biomarkers and therapeutic targets based on the increased FUT8, fucosylated ANXA2 and HSP90B1 after HCV infection. •Altered profiles of N-glycans in the HCVcc-infected Huh7.5.1 cells were analyzed.•Fucosylated N-glycans are significantly elevated after HCV infection.•LCA-binding glycoconjugates are the most increased in HCVcc-infected cells.•Fucosylated ANXA2/HSP90B1 are greatly increased in HCV-infected Huh7.5.1 cells.•FUT8 contributes to the elevated fucosylations of ANXA2 and HSP90B1.